2002
DOI: 10.1152/ajpheart.00235.2002
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 Fatty acids suppress monocyte adhesion to human endothelial cells: role of endothelial PAF generation

Abstract: Monocyte-endothelium interaction is a fundamental process in many acute and chronic inflammatory diseases. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are fish oil-derived alternative (ω-3) precursor fatty acids implicated in the suppression of inflammatory events. We investigated their influence on rolling and adhesion of monocytes to human umbilical vein endothelial cells (HUVEC) under laminar flow conditions in vitro. Exposure of HUVEC to tumor necrosis factor (TNF-α) strongly increased 1) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 38 publications
2
68
0
2
Order By: Relevance
“…Recent studies from our group using -3 fatty acid-incubated endothelial cells showed rapid incorporation of EPA and DHA into the sn-2 position of phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol pool including its PAF precursor subclasses. Moreover, decreased PAF formation was noted under these conditions (30,31). In addition, at the transcriptional level, the NFB has been described as activated by arachidonic acid, but not by EPA (32), and DHA was reported to prevent TNF-␣-mediated activation of NFB (10).…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies from our group using -3 fatty acid-incubated endothelial cells showed rapid incorporation of EPA and DHA into the sn-2 position of phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol pool including its PAF precursor subclasses. Moreover, decreased PAF formation was noted under these conditions (30,31). In addition, at the transcriptional level, the NFB has been described as activated by arachidonic acid, but not by EPA (32), and DHA was reported to prevent TNF-␣-mediated activation of NFB (10).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, therapeutic approaches to reduce expression of CD62L and CD11B have been important strategies to prevent vaso-occlusion in sickle cell disease [50]. In vitro [56,57] and in vivo [13] studies in conditions other than SCD have revealed that supplementation with n−3 resulted in significant reduction in blood cell adhesive molecules. Interestingly, we observed a significant reduction of adhesive molecules in monocytes in the group supplemented with n−3 fatty acids, the finding which denotes improvement in SCD-associated chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…As the percentage of C20:4n-6 did not differ between subjects with and without MetS, we consider phospholipase A2 activity, which generates platelet activating factor (PAF) and PAF-like phospholipids with release of C20:4n-6, to have been accelerated. PAF-like phospholipids are recognized in the atherogenic lipoproteins of small, dense LDL [38][39][40][41] . Zak et al reported that the severity of MetS was associated with the progression of oxidative stress, as evaluated with conjugated dienes in LDL 28) .…”
Section: Discussionmentioning
confidence: 99%